Spatiotemporal Impacts of Urban Structure and Socioeconomic Factors on Carbon Dioxide Emissions: A Case Study of the Yangtze River Delta Urban Agglomeration - Zhechen Zhou; Su Xu; Jun Wang; Haitao Shen (Ecosystem Health and Sustainability)
The economic growth and fast urbanization in China have led to a rise in carbon dioxide (CO2) emissions. Prior research has predominantly concentrated on examining the correlation between social economy, urban structure, and CO2 emissions. However, there has been little comprehensive research that considers the incidental truncation of missing CO2 emission data in underdeveloped cities. Here, we take the Yangtze River Delta urban agglomeration as an example and use the sample selection model to study the spatiotemporal impacts of urban structure and socioeconomic factors on CO2 emissions, based on the unbalanced panel data for the years 2005, 2010, 2015, and 2018. The results show the following: (a) The spatial differentiation of urban structures between cities was obvious, and 4 landscape indices showed significant spatial autocorrelation. (b) CO2 emissions per capita and CO2 emissions per unit of gross domestic product were limited dependent variables and affected by regional development degree, which had incidental truncation. (c) The urbanization rate, complex boundaries, concentration, and expansion of construction land will promote the growth of CO2 emissions, while as the proportion of secondary production and urban fragmentation increases by 1%, CO2 emissions will decline by approximately 0.09% and 1.72%, respectively. (d) Single-centered, highly fragmented models can lead to a surge in CO2 emissions per capita, while continuous urban structures with complex boundaries can reduce CO2 emissions per capita and CO2 emissions per unit of gross domestic product. The research findings emphasize the need to consider urban fragmentation, aggregation, and providing sufficient infrastructures for emission reduction, which establish a foundation for the environmentally friendly design of metropolitan areas.